網路品德教育行為準則建置之研究 Development of E-Character Behavioral Standards - 張志銘 Chih-Ming Chang; 周倩 Chien Chou (National Taiwan Normal University, 2019)
Traditional personal virtue education is insufficient for addressing the contemporary concerns associated with Internet use; thus, e-character education is proposed as an effective method for bridging the concerns in cyberspace and those in the real world. The goals of this study were to establish and verify the behavioral standards that should apply in cyberspace. An open-ended questionnaire was first developed. After collecting discussion posts on an online course in which 140 elementary and junior high school teachers participated, we drafted an initial version of the questionnaire containing 67 behavioral standards in 12 core value categories. Next, to verify these standards and evaluate their importance, we invited 19 experts (character education experts, experienced teachers, and Internet literacy scholars) to form a Delphi-technique group. After three Delphi rounds, 17 experts reached a consensus on the 64 most important behavioral standards that would be applicable to student behavior in cyberspace. Finally, according to the results, this study provides suggestions for curriculum design, policy formulation, and further research on e-character education.